Development of information imperatives of socio-economic development of Ukraine - Pishenina, Tatiana; Vlasova, Katerina (Technology audit and production reserves, 2018)
The object of research is the features of the development and implementation of modern information support systems for managing socio-economic development. One of the most problematic places is determination of the efficiency of an information system. The process of evaluating an information system is associated with the complexity and duration of the implementation of the information management system for enterprise management. The analysis of the current state of information support of enterprise management is conducted. The development of modern information systems allows to reveal the potential possibilities of the socio-economic complex of the state in ensuring sustainable development. The main characteristics of implementation, increase the level of competitiveness of innovative products or services in the application of enterprise management information systems are identified. Information systems stimulate the introduction of innovative processes of rational use of the resource potential, which guarantees the formation of information imperatives and the adoption of progressive management decisions to strengthen Ukraine’s competitive advantages in world markets. The implementation of the information support system in the enterprise is hampered by the influence of endogenous and exogenous factors and is a complex and lengthy procedure. When conducting research, general scientific and special research methods were used: analysis and synthesis, analogies and comparative analysis, the method of decomposition and process detailing. Using these methods, a preliminary analysis of modern information technologies and their implementation into the state management system of the socio-economic complex as a complex economic system was made. And determining the level of risks was carried out and their impact on the management result was assessed. When conducting research, information-innovative approaches to the decision-making process were used. The main directions for efficiency evaluation of socio-economic projects in the implementation of information support systems are identified. These areas allow to evaluate the economic results when creating social events to improve the information support of the management system. As well as the development and implementation of socio-economic projects, taking into account the main resources and factors of production of innovative products. This ensures the possibility of quality control of production costs at each stage of the implementation of information support systems.